1973
DOI: 10.1161/01.res.33.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for the Abnormal Energetics of Pressure-Induced Hypertrophy of Cat Myocardium

Abstract: Depressed myocardial contractility with paradoxically increased oxygen consumption has been demonstrated in previous studies of pressure overload hypertrophy. To determine whether altered mitochondrial respiration participates in the abnormal energetics of this muscle, right ventricular hypertrophy (RVH) was produced in 12 cats by pulmonary artery banding. A polarographic muscle bath was used to study eight control and eight RVH papillary muscles, and the respiration of mitochondria isolated from these right v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
52
5

Year Published

1974
1974
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 41 publications
8
52
5
Order By: Relevance
“…Right ventricular hypertrophy was induced by partially occluding the pulmonary artery with a 3.5-mm internal diameter band. Again, full details ofthis procedure have been published before (14). Cats weighing 1.9-4.7 kg were prepared, and a thoracotomy was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Right ventricular hypertrophy was induced by partially occluding the pulmonary artery with a 3.5-mm internal diameter band. Again, full details ofthis procedure have been published before (14). Cats weighing 1.9-4.7 kg were prepared, and a thoracotomy was performed.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies in which depressed contractile state has been observed, the majority of experiments were performed within 60 days of banding (5,6,8,9). Furthermore, the data from muscles examined after different periods of constriction were generally grouped together.…”
Section: Contractile State Of Hypertrophied Myocardium 1269mentioning
confidence: 99%
“…Furthermore, if slight differences were observed, it would be difficult to conclude that such differences represented alterations in contractile state. The papillary muscles of the banded animals were also slightly larger and therefore more subject to hypoxia and impaired function at higher frequencies of contraction (16 (5,6,8).…”
Section: Contractile State Of Hypertrophied Myocardium 1269mentioning
confidence: 99%
“…Thus it has been shown that the right ventricle is particularly sensitive to pressure overload, with decreases of contractility found even before clinical failure. 7 The abnormalities are still reversible until the development of overt failure. Once failure has ensued, it is no longer reversible.8 In contrast, the left ventricle seems to tolerate both pressure and volume overload for a considerable time before abnormalities of contraction can be detected.9…”
mentioning
confidence: 99%
“…16 Alternatively, this finding may show an inhibition of calcium uptake by, or release from, the sarcoplasmic reticulum in patients with heart failure. 7 (c) The production of cyclic AMP by hypertrophied and failing cardiocytes has also received a great deal of attention. The contractile response of failing myocardium to fi adrenergic stimulation by isoprenaline is subnormal."…”
mentioning
confidence: 99%